2004
DOI: 10.1038/sj.onc.1207889
|View full text |Cite
|
Sign up to set email alerts
|

AP-1 blockade in breast cancer cells causes cell cycle arrest by suppressing G1 cyclin expression and reducing cyclin-dependent kinase activity

Abstract: The AP-1 transcription factor is a central component of signal transduction pathways in many cells, although the exact role of AP-1 in controlling cell growth and malignant transformation is unknown. We have previously shown that AP-1 complexes are activated by peptide and steroid growth factors in both normal and malignant breast cells, and that blocking AP-1 by overexpressing a dominant-negative form of cJun (cJun-DN, TAM67) inhibits breast cancer cell growth both in vivo and in vitro. We hypothesized that T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 36 publications
0
58
0
Order By: Relevance
“…Increased AP-1 activity promotes apoptosis in certain cell types, while promoting survival in others. The ectopic expression of c-Jun or c-Fos can induce apoptosis in mouse fibroblasts, sympathetic neurons and human colorectal carcinoma cell lines (38,39). In this study, apicidin induced the activation of c-Jun but had no effect on the levels of c-Fos protein in both cell lines.…”
Section: Discussionmentioning
confidence: 65%
“…Increased AP-1 activity promotes apoptosis in certain cell types, while promoting survival in others. The ectopic expression of c-Jun or c-Fos can induce apoptosis in mouse fibroblasts, sympathetic neurons and human colorectal carcinoma cell lines (38,39). In this study, apicidin induced the activation of c-Jun but had no effect on the levels of c-Fos protein in both cell lines.…”
Section: Discussionmentioning
confidence: 65%
“…In a human fibrosarcoma cell line, TAM67 inhibits AP-1 activity and arrests cells predominately in the G1 phase of the cell cycle (Hennigan and Stambrook, 2001). AP-1 blockade in breast cancer cells induces G1 cell-cycle block, which is associated with decreases in G1 cyclin expression and cyclin-dependent kinase activity (Liu et al, 2004). Moreover, TAM67 inhibits entrance into the S phase after serum stimulation in colon cancer cells (Suto et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest rather restrictive roles of cJun in the acquisition of anchorage independence in the process of human lung carcinogenesis. In breast and colon cancer cells, however, inhibition of cJun has been shown to induce G1 cell arrest on anchorage-dependent conditions (Liu et al, 2004;Suto et al, 2004). In addition, its effects on in vivo tumour growth of lung cancer cells have not been investigated.…”
mentioning
confidence: 99%
“…Deregulated expression of c-Jun induces immortalised rat fibroblasts to grow in an anchorage-independent fashion (Schütte et al, 1989) depending on the induction of multiple c-Jun target genes Leaner et al, 2003Leaner et al, , 2005Hommura et al, 2004;Katabami et al, 2005). Recent studies reported that specific AP-1 blockade by a dominantnegative mutant of c-Jun, TAM67, inhibited the growth of some types of human cancer cells by causing G1 arrest (Ludes-Meyers et al, 2001;Liu et al, 2004;Suto et al, 2004).…”
mentioning
confidence: 99%